2020
DOI: 10.1002/cpph.77
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Humanized Mice from Peripheral Blood Mononuclear Cells or Cord Blood CD34+ Hematopoietic Stem Cells for Immune‐Oncology Studies Evaluating New Therapeutic Agents

Abstract: The clinical success of immune checkpoint modulators and the development of next-generation immune-oncology (IO) agents underscore the need for robust preclinical models to evaluate novel IO therapeutics. Human immune system (HIS) mouse models enable in vivo studies in the context of the HIS via a human tumor. The immunodeficient mouse strains NOG (Prkdc scid Il2rg tm1Sug ) and triple-transgenic NOG-EXL [Prkdc scid Il2rg tm1Sug Tg (SV40/HTLV-IL3, CSF2)], which expresses human IL-3 and GM-CSF, allow for human C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…43 Other researchers also reported that durability of CD34+ humanized mouse model ranged from 4 weeks to 20 weeks (online supplemental table 2). [44][45][46][47][48] In contrast, our humanized mouse model showed long-term survival and long-lasting humanization status (hCD45+ cells ≥ 25% to mice PBMCs) that was maintained up to 11 months. When the human cancer cell line or PDTX tissues were implanted in our humanized mice, persistent tumorigenicity was confirmed from the early period of 12 weeks up to 11 months from the injection of human HSCs.…”
Section: Discussionmentioning
confidence: 66%
“…43 Other researchers also reported that durability of CD34+ humanized mouse model ranged from 4 weeks to 20 weeks (online supplemental table 2). [44][45][46][47][48] In contrast, our humanized mouse model showed long-term survival and long-lasting humanization status (hCD45+ cells ≥ 25% to mice PBMCs) that was maintained up to 11 months. When the human cancer cell line or PDTX tissues were implanted in our humanized mice, persistent tumorigenicity was confirmed from the early period of 12 weeks up to 11 months from the injection of human HSCs.…”
Section: Discussionmentioning
confidence: 66%
“…The immune system of a humanised mouse model constructed using PBMCs is mainly composed of human T cells. Other key immune subpopulations, such as B cells and dendritic cells, are lacking [30].…”
Section: Discussionmentioning
confidence: 99%
“…The humanized mouse field is in constant progress, with new mouse models being able to resemble more accurately the human immune system. As an example, NSG or NOD/Shi-scid/IL-2Rγ null (NOG) mice that express human cytokines such as G-CSF, GM-CSF, or IL-3, lead to better engraftment, generation and development of the human immune system after injection of human CD34 + stem cells (257,258). Another consideration in designing relevant GBM models is the inoculation site of tumor cells.…”
Section: The Need To Have Immunocompetent Pre-clinical Models That Rementioning
confidence: 99%